EPIC-PHASE: a model to explore irrigation strategies - Santos, A.M (2000)
bstract The erosion productivity impact calculator phase (EPIC-PHASE) model has been used to simulate, using 1972 to 1994 climatic date, two irrigation strategies with a non-limited water supply: (1) a standard strategy based on simple decision rules advisable for moderately deep soils of the Lauragais region (France) and in the Alentejo region (Portugal); and (2) a model strategy based on the daily development of soil water depletion and daily water stress intensity predicted by the model. At Lauragais, the results show that for the same level of yield it would have been possible with the model to save 73 mm on average, equivalent of two irrigations per year, compared to the standard strategy. These savings are due to an increased soil water contribution during the cycle and to an earlier end of the irrigation supply. At Alentejo, the results show that for the same level of yield as obtained with the standard strategy, it would have been possible with EPIC-PHASE model to save 100 mm of water on average, equivalent of two irrigations per year due to an increased use of soil water during the cycle. Although the results are from simulations it is proved that the standard strategy is inadequate. Regarding the environmental impact, the model management allows for an increase in the level of water depletion at harvest, delaying the risk of percolation and nitrogen losses during the refill period. The EPIC-PHASE model proved to be a tool capable of defining an irrigation schedule better adapted to the Mediterranean region.